Clinical Implications of Unmasking Dormant Conduction After Circumferential Pulmonary Vein Isolation in Atrial Fibrillation Using Adenosine: A Systematic Review and Meta-Analysis - Chen, Cheng; Li, Daobo; Ho, Jeffery; Liu, Tong; Li, Xintao; Wang, Zhao; Lin, Yajuan; Zou, Fuquan; Tse, Gary; Xia, Yunlong (Frontiers in Physiology, 2019)
Abstract Purpose Circumferential pulmonary vein isolation (CPVI) is a routine ablation strategy of atrial fibrillation (AF). The adenosine test can be used to unmask dormant conduction (DC) of pulmonary veins after CPVI, thereby demonstrating possible pulmonary vein re-connection and the need for further ablation. However, whether adenosine test could help improve the long term successful rate of CPVI is still controversial. This systemic review and meta-analysis was to determine the clinical utility of the adenosine test. Methods PubMed, EMBASE, Web of Science and Cochrane Library database were searched through July 2016 to identify relevant studies using the keywords “dormant pulmonary vein conduction”, “adenosine test”, “circumferential pulmonary vein isolation” and “atrial fibrillation”. A random-effects model was used to compare pooled outcomes and tested for heterogeneity. Results A total of 17 studies including 5169 participants were included in the final meta-analysis. Two groups of comparisons were classified: (1) Long-term successful rate in those AF patients underwent CPVI with and without adenosine test [Group A (+) and Group A (-)]; (2) Long-term successful rate in those patients who had adenosine test with and without dormant conduction [Group DC (+) and Group DC (-)]. The overall meta-analysis showed that no significant difference can be observed between Group A (+) and Group A (-) (RR 1.08; 95% CI 0.97-1.19; P 0.16; I2 66%) and between Group DC (+) and Group DC (-) (RR 1.01; 95% CI 0.91-1.12; P 0.88; I2 60%). Conclusion Pooled meta-analysis suggested adenosine test may not improve long-term successful rate in AF patients underwent CPVI. Furthermore, AF recurrence may not be decreased by eliminating DC provoked by adenosine, even though adenosine test was applied after CPVI. Keywords Atrial fibrillation. Pulmonary vein isolation. Adenosine. Dormant conduction. Meta-analysis